ECHOCARDIOGRAPHIC CRITERIA FOR PULMONARY ARTERY THROMBOEMBOLISM DUE TO ACUTE MYOCARDIAL INFARCTION - Nurmurzaev Zafar Narbai ugli,; Khaitova Sevara Abdulla kizi, (Journal of new century innovations, 2024)
In order to determine the value of echocardiography in cases of suspected pulmonary embolism in patients with acute myocardial infarction, 152 people were examined, of which 112 were with acute myocardial infarction, 13 were with myocardial infarction complicated by pulmonary embolism, 27 were with pulmonary embolism (PE). against the background of various pathologies, except myocardial infarction. To verify the diagnosis of pulmonary embolism, a modern diagnostic algorithm was used, including lung perfusion scintigraphy. It was found that an increase in the end-diastolic size of the right ventricle, systolic pressure in the pulmonary artery, the presence of paradoxical movement of the interventricular septum, and a decrease in the collapse of the inferior vena cava during inspiration can be considered significant diagnostic signs for suspected pulmonary embolism in acute myocardial infarction. In myocardial infarction complicated by non-massive pulmonary embolism, isolated right ventricular dysfunction was not observed.